To find the equation of the line in the form \( y = mx + b \), we first need to determine the slope (\( m \)) of the line using the two points given, which are \( (0, -3) \) and \( (1, 0) \).
The slope \( m \) can be calculated using the formula:
\[ m = \frac{y_2 - y_1}{x_2 - x_1} \]
Using the points \( (0, -3) \) as \( (x_1, y_1) \) and \( (1, 0) \) as \( (x_2, y_2) \):
\[ m = \frac{0 - (-3)}{1 - 0} = \frac{3}{1} = 3 \]
Now that we have the slope \( m = 3 \), we can use one of the points to find the y-intercept (\( b \)). We'll use the point \( (0, -3) \):
The equation in slope-intercept form is:
\[ y = mx + b \]
Substituting \( m = 3 \) and using the point \( (0, -3) \):
\[ -3 = 3(0) + b \]
Solving for \( b \):
\[ -3 = 0 + b \implies b = -3 \]
Now we can write the equation of the line:
\[ y = 3x - 3 \]
So the final answer for the equation of the line is:
\[ \boxed{y = 3x - 3} \]